Evaluation of the First Incarceration Shock Treatment (FIST) Program for Youthful Offenders in Kentucky, 1993-1994 - Bourque, Blair B. ([Verlag nicht ermittelbar], 1999)
Boot camps, a popular alternative to incarceration, are characterized by a strong emphasis on military structure, drill, and discipline and by an abbreviated period of incarceration. Originally designed for young, adult, male offenders convicted of nonviolent crimes, boot camps have been expanded to encompass juveniles and women as well. In 1992 the Bureau of Justice Assistance funded three agencies to develop correctional boot camps for young offenders, and simultaneously, the National Institute of Justice supported an evaluation of these camps. By October 1993 the only operational boot camp of the three selected sites was the Kentucky Department of Corrections' First Incarceration Shock Treatment (FIST) program. This data collection is an evaluation of the first 18 months of operation of FIST from July 1993 through December 1994. The primary goal of this evaluation was to document the development of the Kentucky boot camp, the characteristics and experiences of the youthful offenders participating in it, and any changes in participants' attitudes and behaviors as a result of it. The evaluation consisted of an extensive case study, supplemented by pre- and post-test comparisons of boot camp offenders' attitudes, physical fitness, and literacy skills, descriptive information about their engagement in legitimate activities during aftercare, and an assessment of the rates, timing, and sources of program attrition. Variables in this collection include entrance and exit dates, sentence, crime type and class, pre- and post-program test scores in math, reading, and language skills, and demographic variables such as age, race, sex, and marital status.